FREQUENCY AND PREVALANCE OF ANOMALIES AND DEFORMATIONS OF DENTOMAXILLARY (DENTOGNATHIC) APPARATUS IN THE TRANSITIONAL PERIOD OF BITE - P.S. Flis; V.V. Filonenko; N.M. Doroshenko (Український стоматологічний альманах, 2018)
Relevance of research. Studies of frequency and prevalence of teeth anomalies and deformities are required to develop the organizational principles of prevention and provide timely specialized medical care. Violations not only harm the child's health, but also adversely affect their adaptation to the social environment.